2012
DOI: 10.1007/s00436-011-2784-7
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant effect of ginsenoside-based nanoparticles (ginsomes) on the recombinant vaccine against Eimeria tenella in chickens

Abstract: An experiment was conducted to study the adjuvant effect of ginsomes on the recombinant profilin in coccidian-infected breeding birds. Three-day-old chickens were vaccinated with Eimeria tenella recombinant profilin antigen (10, 50, and 100 μg per chicken) with or without 50 μg ginsomes per chicken. The boost vaccination was carried out 14 days later. Two weeks after the booster, the chickens were challenged with 1.5 × 10(4) homologous sporulated oocysts. The specific antibody response, lymphocyte proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Recently, exploration of novel vaccines aiming at preventing avian coccidiosis has gradually become a research hot spot. It was reported that several novel delivery vectors could be used as tools to express Eimeria target proteins, mainly including tobacco, ginsenoside-based nanoparticles, Mycobacterium bovis, Bacillus Calmette–Guerin , Bacillus subtilis , and Pichia pastoris ( Sathish et al., 2012 , Zhang et al., 2012 , Wang et al., 2014 , Chen et al., 2015 , Lin et al., 2015 ). Besides the aforementioned delivery tools, lactic acid bacteria are considered to be an ideal oral delivery vector with many advantages, including safety profile, convenient route of oral administration, weak immune response against itself, and establishing specific mucosal immunity ( BaheyEI-Din et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, exploration of novel vaccines aiming at preventing avian coccidiosis has gradually become a research hot spot. It was reported that several novel delivery vectors could be used as tools to express Eimeria target proteins, mainly including tobacco, ginsenoside-based nanoparticles, Mycobacterium bovis, Bacillus Calmette–Guerin , Bacillus subtilis , and Pichia pastoris ( Sathish et al., 2012 , Zhang et al., 2012 , Wang et al., 2014 , Chen et al., 2015 , Lin et al., 2015 ). Besides the aforementioned delivery tools, lactic acid bacteria are considered to be an ideal oral delivery vector with many advantages, including safety profile, convenient route of oral administration, weak immune response against itself, and establishing specific mucosal immunity ( BaheyEI-Din et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…reflected by drug-resistant Eimeria species, drug residues in poultry products and the reversion to virulence for attenuated vaccines. The exploration of novel vaccines has become research hot point, and several delivery tools have been used to deliver target Eimeria proteins, including Escherichia coli (Yin et al, 2015), Bacillus subtilis (Lin et al, 2015), Mycobacterium bovis Bacillus Calmette-Guerin (Wang et al, 2014), attenuated Salmonella enterica serovar Typhimurium (Konjufca, Jenkins, Wang, Juarez-Rodriguez, & Curtiss, 2008), Pichia pastoris (Chen et al, 2015), fowlpox virus (Yang et al, 2008), tobacco (Sathish et al, 2011), nanoparticles (Jenkins et al, 2018;Zhang et al, 2012), Lactobacillus plantarum (Yang et al, 2017), Lactococcus lactis (Li et al, 2018;Ma et al, 2013;Ma et al, 2017), recombinant Eimeria (Tang et al, 2019). Based on our previous study using lactic acid bacteria as a delivery tool, we postulate that the immune responses and efficacies provided by oral immunization of recombinant lactococci could be improved by introducing immune enhancers into the live recombinant bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that E. tenella stimulated CD4+ T cells, macrophage response, and an increase in the IL-2, IL-4, IL-8, IL-10, IL-18, and INF-γ response in the cecum (Cornelissen et al 2009;Zhang et al 2012a). A protective immune response can be stimulated as either a humoralmediated (Th2) response or a cell-mediated (Th1) response, depending on the combination of cytokines generated (Mosmann and Sad 1996).…”
Section: Discussionmentioning
confidence: 99%